Investigating the genetic basis of maize ear characteristics: a comprehensive genome-wide study utilizing high-throughput phenotypic measurement method and system - Wang, Jinglu; Zhao, Shuaihao; Zhang, Ying; Lu, Xianju; Du, Jianjun; Wang, Chuanyu; Wen, Weiliang; Guo, Xinyu; Zhao, Chunjiang (Frontiers in Plant Science, 2023)
The morphology of maize ears plays a critical role in the breeding of new varieties and increasing yield. However, the study of traditional ear-related traits alone can no longer meet the requirements of breeding. In this study, 20 ear-related traits, including size, shape, number, and color, were obtained in 407 maize inbred lines at two sites using a high-throughput phenotypic measurement method and system. Significant correlations were found among these traits, particularly the novel trait ES, which was correlated with traditional traits KNR and KNE. Pairwise comparison tests revealed that the inbred lines of TST were significantly different from other subpopulations in row numbers per ear, kernel numbers per ear and ear color. A genome-wide association study (GWAS) identified 275, 434, and 362 SNPs for Beijing, Sanya, and BLUP scenarios, respectively, explaining 3.78% to 24.17% of the phenotypic variance. Furthermore, 58 candidate genes with detailed functional descriptions common to more than two scenarios were discovered, with 40 genes associated with color traits on chromosome 1. After analysis of haplotypes, gene expression, and annotated information, several candidate genes with high reliability were identified, including Zm00001d051328 for ear perimeter and width, zma-MIR159f for ear shape, Zm00001d053080 for kernel width and row number per ear, and Zm00001d048373 for the blue color channel (B) of maize kernels in the RGB color model. This study emphasizes the importance of researching novel phenotypic traits in maize by utilizing high-throughput phenotypic measurements. The identified genetic loci enrich existing genetic studies related to maize ears.